Exploring the knowledge, attitudes, practices and lived experiences of frontline health workers in the times of COVID-19 : a qualitative study from Bangladesh. Issue 1 (11th January 2022) - Tune, Samiun Nazrin Bente Kamal; Islam, Bushra Zarin; Islam, Mir Raihanul; Tasnim, Zarin; Ahmed, Syed Masud
Abstract : Objective: This study explored Frontline Health Workers' (FLWs) knowledge, attitude and practice (KAP) on COVID-19 and their lived experiences, in both their personal and work lives, at the early stage of the pandemic in Bangladesh. Design, setting and participants: This was a qualitative study conducted through telephone interviews in May 2020. A total of 41 FLWs including physicians, nurses, paramedics, community healthcare workers and hospital support staff from 34 public and private facilities of both urban and rural parts of Bangladesh participated in the interview. A purposive sampling technique supplemented by a snowball sampling method was followed to select the participants. The in-depth interviews followed a semi-structured interview guide, and we applied the thematic analysis method for the qualitative data analysis. Findings: Except physicians, the FLWs did not receive any institutional training on COVID-19, including its prevention and management, in most instances. Also, they had no training in the use of personal protective equipment (PPE). Their common source of knowledge was the different websites or social media platforms. The FLWs were at risk while delivering services because patients were found to hide histories and not maintaining safety rules, including physical distancing. Moreover, inadequate supply of PPE, fear of getting infected, risk to family members and ostracisation by the neighbours were mentioned to be quite common by them. This situation eventually led to the development of mental stress and anxiety; however, they tried to cope up with this dire situation and attend to the call of humanity. Conclusion: The uncertain work environment during the COVID-19 pandemic simultaneously affected FLWs' physical and emotional health in Bangladesh. However, they showed professional devotion in overcoming such obstacles and continued to deliver essential services. This could be further facilitated by a quick and targeted training package on COVID-19, and the provision of supplies for delivering services with appropriate safety precautions.